Evaluating the effectiveness of offshore safety and environmental management systems (Special report (National Research Council (U.S.). Transportation Research Board), 2012)
This report recommends that the Bureau of Safety and Environmental Enforcement (BSEE) take a holistic approach to evaluating the effectiveness offshore oil and the Safety and Environmental Management Systems (SEMS) programs of gas industry operators. According to the report, this approach should, at a minimum, include inspections, audits by the operator and BSEE, key performance indicators, and a whistleblower program. SEMS is a safety management system (SMS) aimed at shifting from a completely prescriptive regulatory approach to one that is proactive, risk based, and goal oriented in an attempt to improve safety and reduce the likelihood that events similar to the April 2010 Macondo incident will reoccur. According to the committee that produced the report, it is not possible for a regulator to create a culture of safety in an organization by inspection or audit; that culture needs to come from within the organization. To be successful, the tenets of SEMS must be fully acknowledged and accepted by workers, motivated from the top, and supported throughout the organization and must drive worker actions. The report also notes that BSEE can encourage and aid industry in development of a culture of safety by the way it measures and enforces SEMS. The committee believes BSEE should seize this opportunity to make a step change in safety culture by adopting a goal based holistic approach to evaluating the effectiveness of SEMS programs. In recommending a holistic approach to evaluating the effectiveness of SEMS programs, the report explores in detail the role of SEMS in helping to develop a culture of safety, highlights the pros and cons of various methods of assessing the effectiveness of a SEMS program, and investigates existing approaches for assessing the SMS programs of various U.S. and international regulatory agencies whose safety mandates are similar to that of BSEE.